2-Deoxyglucose and Newcastle Disease Virus Synergize to Kill Breast Cancer Cells by Inhibition of Glycolysis Pathway Through Glyceraldehyde3-Phosphate Downregulation - Al-Shammari, Ahmed Majeed; Abdullah, Amer Hasan; Allami, Zainab Majid; Yaseen, Nahi Y. (Frontiers in Molecular Biosciences, 2019)
Targeting cancer cells metabolism is promising strategy in inhibiting cancer cells progression that are known to exhibit increased aerobic glycolysis. We used the glucose analog 2-Deoxyglucose (2-DG) as a competitor molecule of glucose. To further enhance the effectiveness of 2-DG, the Newcastle disease virus (NDV) was used as a combination virotherapy to enhance the anti-tumor effect. Human and mouse-breast cancer cells were treated by NDV and/or 2-DG. The effect was analyzed by study cell viability, apoptosis and level of glyceraldehyde3-phosphate (GAPDH) by ELISA and QPCR assays. Synergistic cytotoxicity was found after a 72-h treatment of human- and mouse-breast cancer cells with 2-DG in combination with NDV at different concentrations. The synergistic cytotoxicity was accompanied by apoptotic cell death and GAPDH downregulation and inhibition to glycolysis product pyruvate. The combination treatment showed significant tumor growth inhibition compared to single treatments in vivo. Our results suggest the effectiveness of a novel strategy for anti-breast cancer therapy through glycolysis inhibition and GAPDH downregulation.